MiR-126 Contributes to Human Umbilical Cord Blood Cell Induced Neurorestorative Effects after Stroke in Type-2 Diabetic Mice - Chen, Jieli (Stem Cells, 2016)
Diabetes mellitus (DM) is a high risk factor for stroke and leads to more severe vascular and white-matter injury than stroke in non-DM. We tested the neurorestorative effects of delayed human umbilical cord blood cell (HUCBC) treatment of stroke in type-2 diabetes (T2DM). db/db-T2DM and db/+-non-DM mice were subjected to distal middle cerebral artery occlusion (dMCAo) and were treated 3 days after dMCAo with: 1) non-DM + PBS; 2) T2DM + PBS; 3) T2DM + naïve-HUCBC; 4) T2DM + miR-126(−/−)HUCBC. Functional evaluation, vascular and white-matter changes, neuroinflammation, and miR-126 effects were measured in vivo and in vitro. T2DM mice exhibited significantly decreased serum and brain tissue miR-126 expression compared with non-DM mice. T2DM+HUCBC mice exhibited increased miR-126 expression, increased tight junction protein expression, axon/myelin, vascular density and M2-macrophage polarization; However, decreased blood-brain barrier leakage, brain hemorrhage and miR-126 targeted gene VCAM-1 and MCP-1 expression in the ischemic brain as well as improved functional outcome were present in HUCBC treated T2DM mice compare with control T2DM mice. MiR-126(−/−)HUCBC-treatment abolished the benefits of naïve-HUCBC-treatment in T2DM stroke mice. In vitro, knock-in of miR-126 in primary cultured brain endothelial cells (BECs) or treatment of BECs with naïve-HUCBCs significantly increased capillary-like tube formation, and increased axonal outgrowth in primary cultured cortical neurons; whereas treatment of BECs or cortical neurons with miR-126(−/−) HUCBC attenuated HUCBC-treatment induced capillary tube formation and axonal outgrowth. Our data suggest delayed HUCBC-treatment of stroke increases vascular/white-matter remodeling and anti-inflammatory effects; MiR-126 may contribute to HUCBC-induced neurorestorative effects in T2DM mice.